Hybrid energy storage system for fast and efficient electric vehicle charging - Liew Hui Fang; Muhammad Izuan Fahmi Romli; Rosemizi bin Abd Rahim (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
The rapid adoption of electric vehicles (EVs) necessitates efficient and fast charging solutions to meet growing energy demands. This study introduces a hybrid energy storage system (HESS) designed to enhance EV charging performance. By integrating batteries and supercapacitors, the HESS leverages their complementary characteristics, optimizing energy storage and delivery. The primary problem addressed is the inefficiency and prolonged charging times of conventional EV charging infrastructure. A dynamic control strategy manages power flow between batteries and supercapacitors, significantly reducing charging times and improving system efficiency. This approach reduces battery size and optimizes power quality, utilizing a device with three 18650 lithium-ion batteries and four high-capacity supercapacitors. Simulations using MATLAB/Simulink and Proteus software demonstrate a charging time of 57 minutes for the storage system and 4.74 hours for a full EV battery charge, outperforming traditional methods. This project contributes to the design and implementation of a HESS for EVs, facilitating both efficient and fast charging capabilities.